Pengaruh Jenis Teh Kompos dan Mulsa Organik terhadap Pertumbuhan dan Hasil Tanaman Kacang Mungo (Vigna mungo (L.) Hepper) Var. Lokal Timor - Miryam Kamlasi; Syprianus Ceunfin; Maria Afnita Lelang (Savana Cendana, 2018)
These mungo beans come from India and have been cultivated since ancient times and are one of the most valuable beans in India and Pakistan. Mungo beans in East Nusa Tenggara, especially in South Central Timor District, subdistrict Amanatun Utara known as 'fue metan'. Along with the development era of production fue metan decreased even almost extinct because only a handful of farmers who still maintain save by continuing to cultivate this type of beans. This study aims to determine the effect of compost tea and mulch type on growth and yield of mungo been plant. The design used in this research is Factorial Randomized Block Design, 4 × 3 and repeated 3 times. The first factor is compost tea consisting of four levels namely: without compost tea, compost tea leaf kerinyu, compost tea leaves Gamal, compost tea leaves kerinyu + leaf Gamal and the second factor is the type of organic mulch consists of three levels of control, the organic mulch of grass, mulch organic from sawdust. The results showed that compost tea was able to increase the harvest index by 26-37% from control. Giving mulch on soil increases moisture level indicates better soil binding power so as to increase the weight of crop seeds.